Analysis of Archives Management in SMA Negeri 13 Gowa, Bontonompo Selatan District - Mukarram Syah; Dwi Fuji Lestari Firman (Pinisi Business Administration Review, 2021)
This study aims to determine the implementation of archive management at SMA Negeri 13 Gowa, South Bontonompo District. In this study there are five indicators, namely, receipt of archives, storage of archives, maintenance and security of archives, as well as shrinkage of archives, and destruction of archives. This research method is descriptive qualitative. Data collection techniques used are observation, interviews, and documentation. There were 5 (five) informants in this study. Analysis of the data used is an interactive model. Techniques in analyzing the data are data reduction, data presentation and conclusion drawing. To ensure the validity of the data, extended observations, triangulated data sources, held member checks, and increased persistence in conducting research. The results of this study indicate that the implementation of archive management at SMA Negeri 13 Gowa, South Bontonompo District is still very simple and not in accordance with the development of existing archival science. Judging from the lack of archive management facilities and infrastructure, and the absence of an archive management system that is used to organize archives, so, to rediscover an archive it still takes a long time and sometimes it has to be archived. So, in this case, archive management is considered less than optimal and ineffective. and the absence of an archive management system that is used to organize archives so that, to rediscover an archive it still takes a long time and sometimes it has to be archived. So, in this case, archive management is considered less than optimal and ineffective. and the absence of an archive management system that is used to organize archives so that, to rediscover an archive it still takes a long time and sometimes it has to be archived. So, in this case, archive management is considered less than optimal and ineffective.